MANAJEMEN KURIKULUM PAUD BERBASIS ALAM (Studi Kasus di Paud Alam Ar-Ridho Semarang Tahun Pelajaran 2013/2014) - Mughiyati, Jayanti; Waluyo, Edi (BELIA: Early Childhood Education Papers, 2014)
Curriculum management is a management of curriculum to develop childrens intelligence. The curriculum management of nature-based school has differences with the management of the school curriculum in general. The purpose of the study is to describe the curriculum management of nature-based early-childhood education institution Ar-Ridho and to describe the involvement of teachers, parents, school committees, and people around in the curriculum management of nature-based early-childhood education institution Ar-Ridho. The study used a qualitative approach with case study research design. The subjects of the study as the source of data were: principals, teachers, parents, school committees, and people around. Methods of collecting data were: observation, interviews, and documentation. Besides, this study used stages of data collection, data reduction, data presentation, and drawing conclusions as the data analysis techniques. Validity of the data was source triangulation techniques and triangulation methods. The results of the study can be summarized as follows curriculum management of nature-based early-childhood education institution Ar-Ridho includes planning to compose lesson plans of spider web, weekly, daily and children worksheets. The management, selection, and development of themes and indicators was adjusted with the school of nature. Sub-themes used directly introduce children to the subject in nature. In the learning inside or outside the class, nature as the green lab and character building for caring the environment are taught by small habituations. Evaluation of the curriculum is done once a year by the director, principals, and teachers by looking the vision and mission of the school. The involvement of teachers, parents, and school committees in the curriculum management could be seen by inviting parents in the theme changing and discussing about child development. Moreover, school committees provide both funds and personnel support during the implementation of teaching and learning process. However, the involvement of people around in the curriculum management has not been seen yet.